Thoracic extradural meningioma mimicking lumbar canal stenosis: A case report - Pokharel, Sabin; Pathak, N; Adhikari, S; Paudel, Sushil; Pokharel, Rohit Kumar (Nepal Orthopaedic Association Journal, 2020)
Pure extradural meningioma is a rare condition. Clinical presentation of thoracic extradural meningioma may mimic lumbar canal stenosis, and there are reports on paraplegia due to missed thoracic meningioma following lumbar canal decompression surgery. We report a case with long history of low back pain radiating to both legs with weaknesses, initially diagnosed as lumbar canal stenosis. On further clinical evaluation revealed features of upper motor neuron lesion in lower limbs, not corroborating to the initial diagnosis. Screening MRI of whole spine showed thoracic extradural meningioma. The tumor was enucleated and the cord was decompressed. Post operatively, there was excellent neurological improvement without recurrence till last follow up of one year. Thorough clinical evaluation of cases and adequate imaging keeping differential diagnosis of rare lesions can avoid missing such conditions.